Self-Efficacy (SE) and Motivation of the Indonesian Teacher Educator Authors (TEAs) in Writing Articles for Publication: The Bloom Digital Taxonomy (BDT) Perspective - Dedi Turmudi; Muhammad Ihsan Dacholfany; Ummi Rasyidah (National Research University Higher School of Economics, 2024)
Background: Writing articles is inevitable for Teacher Educator Authors (TEAs) at the university level, and many studies reported writing articles for publication. However, self-efficacy (SE) and motivation in writing scientific articles by higher education teachers remained unexplored compared to the Bloom Digital Taxonomy (BDT). Purpose: This study explored self-efficacy (SE) as well as intrinsic and extrinsic motivation (IM & EM) in writing articles for publication by Teacher Educator Authors (TEAs) in the light of the Bloom Digital Taxonomy (BDT). Furthermore, it measured how prior empirical evidence and current findings are presented in the Bloom Digital Taxonomy (BDT). Method: The design used qualitative descriptive content data from an ethnographic study, and 21 Teacher Educator Authors (TEAs) of English in Indonesia with specific characteristics were purposively selected. The participants constituted state and private universities in Java, Sumatra, Borneo, and Celebes. Data were collected through questionnaire, in-depth interviews, and electronic observation. The participants were then requested to complete a Google Form, and directly interviewed electronically and physically. The questionnaire data were subsequently addressed in the in-depth interview. This study utilised the Criteria Content Analysis (CCA) method and exploratory-provisional coding to analyse the transcription data.    Results: The results showed that self-efficacy (SE) features were mainly related to profession, self-development, and attributes of Teacher Educator Authors (TEAs). Furthermore, self-esteem, expertise markers, and a way to learn dominated intrinsic motivation (IM), while appreciation, shaping expertise, and seeking dignity dominated the extrinsic. The findings were in the high order of affective skills (HOAs) with valuing (A3) and internalising (A5). The study had practical implications that writing for scholarly publications should inevitably be part of the curriculum in higher education, and grants should increase to maintain the internalisation of Teacher Educator Authors (TEAs) in producing articles. In addition, the results contributed to the theoretical implication that HOAs, valuing, and internalising dominated roles in creating quality articles at any level.